Human transmissible spongiform encephalopathies in eleven countries: diagnostic pattern across time, 1993-2002 - Jansen Gerard H; Lewis Victoria; Collins Steven; Sanchez-Juan Pascual; Van Duijn Cornelia; Alpérovitch Annick; Delasnerie-Lauprêtre Nicole; Brandel Jean-Philippe; Kretszchmar Hans A; Zerr Inga; Pocchiari Maurizio; Puopolo Maria; et al. (BMC, 2006)
Abstract Background The objective of this study was to describe the diagnostic panorama of human transmissible spongiform encephalopathies across 11 countries. Methods From data collected for surveillance purposes, we describe annual proportions of deaths due to different human transmissible spongiform encephalopathies in eleven EUROCJD-consortium countries over the period 1993-2002, as well as variations in the use of diagnostic tests. Using logistic models we quantified international differences and changes across time. Results In general, pre-mortem use of diagnostic investigations increased with time. International differences in pathological confirmation of sporadic Creutzfeldt-Jakob disease, stable over time, were evident. Compared to their counterparts, some countries displayed remarkable patterns, such as: 1) the high proportion, increasing with time, of variant Creutzfeldt-Jakob disease in the United Kingdom, (OR 607.99 95%CI 84.72-4363.40), and France (OR 18.35, 95%CI 2.20-152.83); 2) high, decreasing proportions of iatrogenic Creutzfeldt-Jakob disease in France, (OR 5.81 95%CI 4.09-8.24), and the United Kingdom, (OR 1.54 95%CI 1.03-2.30); and, 3) high and stable ratios of genetic forms in Slovakia (OR 21.82 95%CI 12.42-38.33) and Italy (OR 2.12 95%CI 1.69-2.68). Conclusion Considerable international variation in aetiological subtypes of human transmissible spongiform encephalopathies was evident over the observation period. With the exception of variant Creutzfeldt-Jakob disease and iatrogenic Creutzfeldt-Jakob disease in France and the United Kingdom, these differences persisted across time.